2018
DOI: 10.3892/etm.2018.6926
|View full text |Cite
|
Sign up to set email alerts
|

Changes in TNF-α, IL-6, IL-10 and VEGF in rats with ARDS and the effects of dexamethasone

Abstract: Changes in tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), IL-10 and vascular endothelial growth factor (VEGF) in serum and bronchoalveolar lavage fluid (BALF) in rats with acute respiratory distress syndrome (ARDS) and the intervention effect of dexamethasone were observed to explore the theoretical basis of dexamethasone in the treatment of ARDS. Seventy-two rats were randomly divided into normal control group (group N, n=24), ARDS model group (group L, n=24) and dexamethasone group (group D, n=24). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 28 publications
3
34
0
1
Order By: Relevance
“…In this study, DEX administration decreased levels of pro-inflammatory cytokines in the lung and plasma compared to the ARDS group, while the higher dose DEX-1.0 had slightly stronger impact on these changes. The effectiveness of dexamethasone in reducing levels of cytokines was observed also by other authors (Xinmin et al 2006, Qin andQiu 2019).…”
Section: Nt Tbarssupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, DEX administration decreased levels of pro-inflammatory cytokines in the lung and plasma compared to the ARDS group, while the higher dose DEX-1.0 had slightly stronger impact on these changes. The effectiveness of dexamethasone in reducing levels of cytokines was observed also by other authors (Xinmin et al 2006, Qin andQiu 2019).…”
Section: Nt Tbarssupporting
confidence: 76%
“…, Beck et al 2009, Newton et al 2010 and their role was found in favor of treatment of ARDS (Peter et al 2008). There are evidences for the beneficial role of dexamethasone (DEX) in ARDS condition (Villar et al 2016, Qin andQiu 2019), particularly for low dose of DEX (Lee et al 2005, Xinmin et al 2006, Wang et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…MPO expressed in neutrophil granules is a major mediator of lung injury. Neutrophils also secrete some cytokines such as TNF-α, IL-1β, and IL-6 to deteriorate ARDS [51]. An attenuation of ARDS by nanoparticulate OA was found, based on the reduction of MPO and cytokines.…”
Section: Discussionmentioning
confidence: 94%
“…Cytokines can be produced by different immune cells. For instance, IL-6 is a key proinflammatory mediator secreted by neutrophils, macrophages, and T cells to induce an inflammatory cascade in ARDS [51]. Alveolar macrophages are important phagocytic cells in the lung for nanoparticle internalization.…”
Section: Discussionmentioning
confidence: 99%
“…After PBLI, the alveolar epithelium and alveolar capillaries are exposed to high concentrations of VEGF, which increase the vascular permeability, resulting in an increased inflammatory response during the exudation period and exacerbating the condition of PBLI [ 102 ]. Qin et al [ 103 ] found that in the ARDS model, levels of TNF-α, IL-6, and VEGF in bronchoalveolar lavage fluid (BALF) were significantly higher than those of the control group, resulting in an imbalance between pro-inflammatory and anti-inflammatory responses. In addition, Lin et al [ 98 ] suggested that VEGF participates in fat embolism (FE)-induced ALI via VEGFR-2 and MAPK cascade, which induce IL-1β release and inducible nitric oxide synthase (iNOS) upregulation ( Figure 3 ).…”
Section: Damps and Their Signaling Pathways Related To Pblimentioning
confidence: 99%